Advances in the Synthesis and Superconductivity of Lanthanide Polyhydrides Under High Pressure - Guo, Jianning; Chen, Su; Chen, Wuhao; Huang, Xiaoli; Cui, Tian (Frontiers in Electronic Materials, 2022)
Room-temperature superconductors have long been the ultimate goal of scientists. Pressure-stabilized hydrides are a new rapidly growing class of high temperature superconductors, which is believed to be a new superconducting system, and has undoubtedly led to a surge in the discovery of new hydrogen-rich materials. They are the forefront of physics and materials science. Lanthanide polyhydrides formed under pressure are promising conventional superconductors. Especially, recently both of theoretical and experimental reports on lanthanum hydrides under pressure exhibiting superconductivity at temperatures as high as 250 K have further stimulated an intense search for room-temperature superconductors in hydrides. This review focuses on the recent advances of crystal structures, stabilities, and superconductivity of lanthanide polyhydrides at high pressures, especially the experimental results from our group. By using in situ electrical resistance measurements, we have got several high-temperature superconducting phases: lanthanum superhydride and two cerium superhydrides., The present work discovers that superconductivity declines along the La-Ce-Pr-Nd series, while magnetism becomes more and more pronounced. These discoveries have enriched the binary system of clathrate superhydrides and provided more hints for studying the role of rare earth metal elements in high-temperature superconductivity.